Perspectives - PATKÓ, Éva (Presa Universitară Clujeană, 2024)
This book is dedicated to students interested in theater and to fellow colleagues around the world from whom I’ve gotten so much inspiration. Theater has the gift of creating new worlds, new languages on stage. My belief is that we must continue creating visionary worlds, universes that could not exist anywhere else but on stage. This is indeed a privilege, to dream of other realities than our own, realities that reflect – with the help of the spectator – on how our present realities are impoverished by a lack of imagination. Artistic activity is a reflection on reality, the process of thinking about reality and not merely an intellectualization of it. The spectator comes up with their own understanding and interpretation by employing their personal imagination and life experiences to relate to what is seen on stage. In the process of understanding theater it is more important to explore than to understand.